AIRPORT NOISE LEVEL AND ITS EFFECT ON BLOOD PRESSURE ON THE GORONTALO COMMUNITY - Ekawaty Prasetya; Zul Fikar Ahmad; Siti Surya Indah Nurdin (Jambura Journal of Health Sciences and Research, 2022)
The rapidly increasing flight activity affects the health of the population living, traveling, and working around or at airports. Noise generated by aircraft causes physiological and psychological disturbances. This study aims to assess the effect of noise on increasing blood pressure. The research was conducted in Tolotio Village, Gorontalo Regency in 2019. Respondents were selected using a purposive sampling technique. The Noise was collected using a Sound Level Meter, and blood pressure was collected using a sphygmomanometer. Data were analyzed using One Way Anova statistical test. The results of the analysis showed that there was a significant difference in the systolic blood pressure of the respondents who lived in the three sampling locations with p-value = 0.016 = 0.05. However, for diastolic blood pressure, there was no significant difference between respondents who lived in the three sampling locations p-Value = 0.670 = 0.05. It is recommended to provide education about the dangers of airport noise for public health.